2016
DOI: 10.1109/tetc.2015.2389662
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Analysis of RRC-Based Signalling Storms in 3G Networks

Abstract: Mobile networks are vulnerable to signaling attacks and storms that are caused by traffic patterns that overload the control plane, and differ from distributed denial of service attacks in the Internet since they directly affect the control plane, and also reserve wireless bandwidth and network resources without actually using them. Such storms can result from malware and mobile botnets, as well as from poorly designed applications, and can cause service outages in 3G and 4G networks, which have been experienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 56 publications
0
36
0
Order By: Relevance
“…In this section, we evaluate the performance of our detection technique using the mobile network simulator developed in [39,40]. We first present the traffic models that characterize the normal user behavior, and two attack models that represent both malicious and misbehaving UEs.…”
Section: Experiments and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this section, we evaluate the performance of our detection technique using the mobile network simulator developed in [39,40]. We first present the traffic models that characterize the normal user behavior, and two attack models that represent both malicious and misbehaving UEs.…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…Then we discuss the results of applying the algorithm on the dataset produced by the simulator. Since the impact of signaling storms on mobile networks has been analyzed extensively in [4,21,40], the objective of the present simulation setup is to evaluate the performance of our detection algorithm, and therefore only a small scenario has been considered. In particular, we simulated 200 3G/UMTS UEs in an area of 2 × 2 km 2 which is covered by 7 base stations connected to a single radio network controller (RNC).…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…Network worms were also considered, and CPN was used to reroute the users' traffic to avoid the infected nodes (Sakellari and Gelenbe [176], Sakellari, Hey, and Gelenbe [177]). Further research on network security can be found in (Gelenbe et al [87], Gorbil et al [151], Yu et al [185]). …”
Section: Autonomic Systems and Cognitive Packet Network (Cpns)mentioning
confidence: 99%
“…In this section we evaluate the performance of the joint detection and mitigation approach that we have proposed using the mobile network simulator described in [21,22]. We illustrate how the proposed scheme allows quick reaction to malicious signaling behaviors or to malfunctioning applications, by showing the temporal behavior of network signaling load and delay during normal operation and then during an attack which is being detected and mitigated with our approach.…”
Section: Simulation Experimentsmentioning
confidence: 99%
“…This type of behavior on wireless networks can result in abusive bandwidth occupancy, excessive signaling at the mobile operator [2,22], battery dissipation at mobile devices [14], and extra energy consumption in base stations and backbone networks [18,17,34]. If mobile technology is exploited in cyber-physical infrastructures such as the smart grid, or for the Internet of Things (IoT) including vehicular technologies, smart homes, and emergency management systems [20], such signaling storm effects can delay or impair communications which are of vital importance.…”
Section: Introductionmentioning
confidence: 99%